Smart Game for Sex Education: Pengembangan Media untuk Meningkatkan Pendidikan Seksual Anak - Tursina, Ade; Veryawan; Vira Adelia (PAUD Lectura: Jurnal Pendidikan Anak Usia Dini, 2025)
The purpose of the SGSE (Smart Game for Sex Education) media in improving sexual education for children includes the introduction of the boundaries of genitals between men and women, the introduction of body parts that may be touched and may not be touched, and the introduction of normal emotional reactions. The subjects in this study were validators of material experts, media experts, language experts, and 9 children at TAUD Luqmanul Hakim Kindergarten. The results of the material expert validity test obtained a percentage of 92% with the category of "very feasible". The results of the media expert validity test obtained a percentage of 94% with the category of "very feasible", and the results of the language expert validity test obtained a percentage of 92% with the category of "very feasible" then strengthened by the results of media trials in early childhood through individual trials with a percentage obtained of 83.33% and small group trials with a percentage obtained of 93%, the results of both trials are included in the criteria of "developing very well". So it is concluded that the SGSE (Smart Game for Sex Education) media is feasible and effective for improving sexual education for children aged 5-6 years.